Product innovation & customer satisfaction in Fairy Hot Bread & Cake House Branch Changlon - Mohd Alwi, Muhammad Shahizdan; Sawal, Syaidah Syahirah; Rosman, Nur Amirah; Ramli, Nor Hafizah; Murad, Siti Zuhaira; Ibrahim, Jafni Azhan (2015)
The main purpose of this study was to investigate variables that influence the innovation and customer satisfaction at Fairy Hot Bread & Cake House in Changloon, Kedah.Besides that, this study also was conducted to identify the factors that influence the buying decision of the customers and to provide suggestions to Fairy Company according to customer behaviour towards innovative products.The innovation factors involved were technology, product variety and standardize recipe.Customer satisfaction became as mediating variable and while, customer loyalty became as dependent variable since it was derived from customer satisfaction.Respondents covered potential buyers surrounding University Utara Malaysia’s students who were randomly selected. The theory of customer satisfaction model was used in this study to support the innovation factors towards customer satisfaction. Hundred (100) sets of questionnaire were distributed to the targeted respondents.The data was analysed by using Statistical Package for the Social Sciences (SPSS) software.Hence, this study expected that the results would have positive impact on Fairy to improve its offerings.